Tight nuchal cord and neonatal hypovolaemic shock. - Vanhaesebrouck, P (1987)
Two neonates who went into acute hypovolaemic shock due to a tight nuchal cord were successfully resuscitated. The occurrence of this life threatening complication in two low risk pregnancies emphasises the importance of having staff trained in resuscitation immediately available in the delivery unit.